2006
DOI: 10.1002/jbm.a.30792
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of bisphosphonate onto hydroxyapatite using a novel co‐precipitation technique for bone growth enhancement

Abstract: Premature bone resorption and remodeling by osteoclasts can limit the longevity of implant fixation and recovery time. Orally administered bisphosphonates (BPs) have been used to inhibit osteoclast action at the implant/bone interface. Ideally, these should be delivered at the interface with the osteoblast-active hydroxyapatite (HA) for maximum effect. This investigation introduces a novel BP loading technique to achieve improved BP release from a simulated body fluid-grown HA (SBF-HA) with the aim of improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 41 publications
0
17
2
Order By: Relevance
“…Srisubut et al (33) reported that a single dose of local delivery of alendronate improved bone formation. it can be hypothesized that the topical application of alendronate will modify the local osteclastic activity and thereby slow down the bone resorption during initial modeling (22), leading to better bone formation in the defect area, although in our study, topically applied alendronate did not enhance significantly the local bone conditions. in both groups, a notable increase in the number of osteoclasts was observed between the 2-week and 4-week periods (P < 0.05).…”
Section: Resultscontrasting
confidence: 76%
“…Srisubut et al (33) reported that a single dose of local delivery of alendronate improved bone formation. it can be hypothesized that the topical application of alendronate will modify the local osteclastic activity and thereby slow down the bone resorption during initial modeling (22), leading to better bone formation in the defect area, although in our study, topically applied alendronate did not enhance significantly the local bone conditions. in both groups, a notable increase in the number of osteoclasts was observed between the 2-week and 4-week periods (P < 0.05).…”
Section: Resultscontrasting
confidence: 76%
“…10 In this way, the lack of this enzyme will dominate the bone repair equilibrium of bone resorption and formation. It can be hypothesized that the topical application of alendronate will modify the local osteoclastic activity and thereby slow down the bone resorption during initial remodeling, 12 leading to better bone formation around the implant, although in the present study, topically applied alendronate did not enhance the local bone conditions around In the 6-week group, bone contact was significantly (*) higher in the plain implants than in the alendronate and omeprazole groups. After 12 weeks, the alendronate implants showed significantly (**) less bone contact than the other groups.…”
Section: Discussioncontrasting
confidence: 48%
“…11 However locally applied bisphosphonates have also been shown to influence bone resorption. [12][13][14][15][16][17][18] In addition to the use of bisphosphonates, the activity of the proton pumps can be directly targeted. Omeprazole is a gastric PPI used for the treatment of acid-related diseases, including gastroesophageal reflux and peptic ulcer diseases.…”
Section: Introduction Bmentioning
confidence: 99%
“…159 CaPs, most commonly HA, have been used to generate thin coatings on the surface of titanium implants. 60,131,159,158,160,161,165 The most common strategy that produces the chemical association of BPs with the CaPs coating is by soaking the implants in a BPs solution (Fig. 3) 60,131,[158][159][160][161][162][163][164] Other strategies that produce the chemical association of BPs with CaPs reported include bisphosphonate adsorption onto plasma-sprayed HA and simulated body fluidgrown HA coatings that are commonly used for orthopedic implants.…”
Section: Role Of Bps As Coatings For Improved Fixation Of Orthopedic mentioning
confidence: 99%